Upper Extremity Function Following Transradial Percutaneous Coronary Intervention: Results of the ARCUS Trail - Muhammad Ijaz Khan, Shireen Shah, Hamza Ashfaq, Muhammad Kashif Rafiq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Regardless of the recent rise in the number of articles published on transradial access (TRA) for diagnostic coronary intervention and complications of the upper extremity may be underestimated. The aim of this study to investigate the prevalence of upper extremity disorder by comparing the transradial and transfemoral artery percutaneous coronary intervention (TR-PCI). Study Design: This was cross-sectional study and conducted in the Ayub teaching hospital Abbotabad, for six months July 2022 to December 2022. Materials and Methods: The total participants were 250 which included 200 TRA and 50 TFA participants and involving any type of cerdiointervention, thrombectomies for acute ischemic stroke, and carotid artery stents. The participants were selected by sampling technique were interviewed in the Khyber teaching hospital Peshawar. We analyzed dependent and independent variables. Data analysis statistically by SPSS 22 version. The upper extremity scores were analyzed using Chi-squared test. Results: There were total 250 participants which include 80%TRA and 20% TFA in this research. The majority of the participants in TRA were in the age group (59.2±6.7) years and in TFA group (55.5±7.1) years. The baseline characteristics of the total participants was no significant difference between transradial artery (TRA) and transradial femoral artery (TFA). During follow-up, Cochran's Q-test revealed a significant increase in UED in the intervention extremity of the TRA group p=0.003 and in the TFA group's right upper extremity (p=0.001). During follow-up, 1% TRA participants had RAO, which recanalized over time. Three weeks after the procedure, 10% of participants in the TRA group were referred to a hand specialist then TFA participants. Conclusion: Transradial arterial access (TRA) for percutaneous coronary artery intervention has been linked to lower access site complication rates and higher patient satisfaction when compared to transfemoral access (TFA) after 3 weeks follow up. Keywords: Transradial artery (TRA), Transfemoral artery (TFA), Rotational acetabular osteotomy (RAO).